Direct detection of Marek’s disease virus in poultry dust by loop-mediated isothermal amplification - Woźniakowski, Grzegorz (Springer Vienna, 2014)
Marek’s disease virus (MDV) is a serious concern for poultry production and represents a unique herpesvirus model. MDV can be shed by doubly infected chickens despite vaccination. The fully infectious MDV particles are produced in the feather follicle epithelium (FFE), and MDV remains infectious for many months in fine skin particles and feather debris. Molecular biology methods including PCR and real-time PCR have been shown to be valuable for the detection of MDV DNA in farm dust. Recently, loop-mediated isothermal amplification (LAMP) was found to be useful in the detection of MDV in feathers and internal organs of infected chickens. LAMP is also less affected by the inhibitors present in DNA samples. Taking into account the advantages of LAMP, direct detection of MDV DNA in poultry dust has been conducted in this research. The detection of MDV DNA was possible in 11 out of the 12 examined dust samples without DNA extraction. The DNA was retrieved from dust samples by dilution and incubation at 95 °C for 5 min. The direct detection of MDV DNA in the dust was possible within 30 min using a water bath and UV light. The results were confirmed by electrophoresis and melting curve analysis of the LAMP products. Our results show that LAMP may be used to test for the presence of virulent MDV in poultry farm dust without DNA extraction.